The Arches of Chinatown: Identity, Agency, and Belonging in Vancouver 1896–1936 - Abbott, Frank (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2019)
The British Columbia Chinese community struggled against political and economic racism and discrimination in the first half of the twentieth century. This study focuses on four festive civic celebrations in the period 1896-1936 when Vancouver’s Chinese Canadians employed traditional Chinese culture to assert their place as a legitimate component of the city’s social fabric. They joined official Vancouver in greeting China’s most respected statesman in 1896; participated in civic celebrations for visiting members of Britain’s royal family in 1901 and 1912; and organized one of the most successful aspects of Vancouver’s 1936 fiftieth anniversary celebrations, a four-week “Chinese Carnival.” Voices in the “white” community during the same period steadily but slowly articulated increased levels of acceptance of the Chinese presence. Changes in the popular journalistic portrayal of Chinese people reveal a gradual lessening of racist tropes and stereotypes. Finally, an English-language pamphlet produced in the Chinese community for the carnival provides a glimpse of how Canadian-born Chinese Canadians themselves were forging an increasingly North American identity, undermining arguments about their “inability” to adapt to Canadian cultural values.